2001
DOI: 10.1098/rspb.2001.1610
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variation and language replacements in the Caucasus

Abstract: Sequences of the ¢rst hypervariable segment of the mitochondrial DNA (mtDNA) control region were obtained from 353 individuals representing nine groups and four major linguistic families (IndoEuropean, Altaic and North and South Caucasian) of the Caucasus region. The diversity within and between Caucasus populations exceeded the diversity within Europe, but was less than that in the Near East. Caucasus populations occupy an intermediate position between European and Near Eastern populations in tree and princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 23 publications
4
77
3
Order By: Relevance
“…The clustering of groups on the basis of geographic rather than linguistic relationships is in keeping with previous studies of genetic diversity among Caucasian populations. 10,11 However, the complete mtDNA genome sequences do reveal some additional genetic similarity between the two Turkic-speaking groups (Azeri and Turks) that was not evident in previous studies. Presumably, the sharing of some Central Asian mtDNA haplogroups by Azeri and Turks (Table 3) accounts for this signal of genetic similarity between the Azeri and the Turks.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The clustering of groups on the basis of geographic rather than linguistic relationships is in keeping with previous studies of genetic diversity among Caucasian populations. 10,11 However, the complete mtDNA genome sequences do reveal some additional genetic similarity between the two Turkic-speaking groups (Azeri and Turks) that was not evident in previous studies. Presumably, the sharing of some Central Asian mtDNA haplogroups by Azeri and Turks (Table 3) accounts for this signal of genetic similarity between the Azeri and the Turks.…”
Section: Discussionmentioning
confidence: 55%
“…mtDNA studies reveal a high level of diversity, exceeding that within all of Europe and only slightly lower than West Asian mtDNA diversity, which might indicate an old age of human populations from this region. 10 Overall, the Caucasus groups showed greater similarity with West Asian than with European groups for both genetic systems, although this similarity was much more pronounced for the Y chromosome than for mtDNA, suggesting that recent male-mediated migrations from West Asia have influenced the genetic structure of Caucasus populations. 11 Previous studies of complete mtDNA genome sequences have in general first obtained HV1 sequences (and sometimes, genotyped some haplogroup-defining SNPs), and then selected particular individuals of interest for complete mtDNA genome sequencing.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…16,17 In the efforts to gain a comprehensive understanding of the impact that complex historical migrations and events have had upon the genetic structure of populations, the human Y-chromosome has emerged as a highly effective tool. 18 Prior examinations of the paternal lineages within Armenia have revealed population-expansion times corresponding to the Neolithic emergence of agriculture, 19 as well as genetic affinities toward both Near Eastern and European populations; 20,21 results that are largely corroborated by mitochondrial DNA 22 and Alu insertion (PAI) studies. 23 It should be noted, however, that the above-mentioned patrilineal studies are hindered by their utilization of a limited set of Y-chromosomal markers that severely restricted their ability to define phylogenetic relationships.…”
Section: Introductionmentioning
confidence: 82%
“…[9][10][11] Others suggest that the genetic legacy of the Caucasus region is mainly because of the people who crossed or invaded this territory in historic times. 12 A large amount of genetic data on the Caucasian populations, based on classical markers, 9,[13][14][15] Alu insertion polymorphisms, 10 mitochondrial DNA 10,16 and the non-recombining portion of the Y chromosome (NRY) 17 have shown that neither geography nor linguistics have had a strong influence on the genetic structure of these ethnic groups and that genetic drift appears to be the main factor acting in the region. Furthermore, Y chromosomes of highland Dagestan ethnic groups appear to have undergone genetic drift independently of the population history of mitochondrial and autosomal loci, suggesting that social rules, and not simply geographic isolation, are the causal agents for the high NRY diversity observed among highlanders.…”
Section: Introductionmentioning
confidence: 99%